2010
DOI: 10.1111/j.1749-7345.2010.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Live Baker's Yeast, Saccharomyces cerevisiae, in Practical Diet to Enhance the Growth Performance of Galilee Tilapia, Sarotherodon galilaeus (L.), and Its Resistance to Environmental Copper Toxicity

Abstract: The potential use of dietary probiotics to enhance the growth and health of aquatic animals has recently attracted intensive attention. Therefore, this study was conducted to evaluate the growth response of Galilee tilapia, Sarotherodon galilaeus (L.), and its resistance to waterborne copper toxicity. Fish (2.5–3.3 g) were fed a diet containing either 0.0 or 10 g live yeast, Saccharomyces cerevisiae, for 6 wk. After the feeding trial, fish at both diets were exposed to 0.0 or 1 ppm Copper (Cu) for 24 h, or 5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…Following dietary S. cerevisiae administration, improved body composition has not been consistently observed [10,12,22,23]. Li et al (2005) showed that whole-body composition of juvenile red drum (Sciaenops ocellatus) was not significantly affected by dietary supplementation with partially autolyzed S. cerevisiae [10].…”
Section: Discussionmentioning
confidence: 93%
“…Following dietary S. cerevisiae administration, improved body composition has not been consistently observed [10,12,22,23]. Li et al (2005) showed that whole-body composition of juvenile red drum (Sciaenops ocellatus) was not significantly affected by dietary supplementation with partially autolyzed S. cerevisiae [10].…”
Section: Discussionmentioning
confidence: 93%
“…Yeast S. cerevisiae produced a better growth performance and feed efficiency of Nile tilapia than a combination of the probiotics Streptococcus faecium and L. acidophilus did [37]. This yeast also improved the growth performance of Galilee tilapia [20].…”
Section: Increase Growth and Survival Ratesmentioning
confidence: 94%
“…thermophilus (previous name Streptococcus thermophilus) [29]. Baker's yeast (Saccharomyces cerevisiae) has been recognized as a potential probiotic for Nile tilapia [15,32,36,37] and Galilee tilapia [20]. Live microalgae also act as a probiotic for tilapia.…”
Section: Sources Of Probioticsmentioning
confidence: 99%
See 2 more Smart Citations